2012
DOI: 10.1111/j.1533-8525.2011.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Confrontations and Donations: Encounters between Homeless Pet Owners and the Public

Abstract: This study examines the interactions between homeless pet owners and the domiciled public with a focus on how the activities of pet ownership help construct positive personal identities. Homeless people are often criticized for having pets. They counter these attacks using open and contained responses to stigmatization. More often, they redefine pet ownership to incorporate how they provide for their animals, challenging definitions that require a physical home. Homeless pet owners thus create a positive moral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…For example, after systematically reviewing the medical records of over 300 of Community Veterinary Outreach patients (to veterinarians, animals are the "patients", and the pet owners are "clients"), we found that 73 % of our patients were in ideal body condition score, compared to the household pets in the U.S. where it is estimated that 52.6 % of dogs and 57.6 % of cats are clinically overweight (2013 National Pet Obesity Awareness Day Survey 2014). In fact, studies have shown that most homeless pet guardians do not have trouble feeding their animal companions (Irvine et al 2012). In a survey of 332 homeless youth in Los Angeles, only 10.42 % of respondents indicated that it was hard to get pet food (Rhoades et al 2014).…”
Section: Companion Animals Of Street-involved Youthmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, after systematically reviewing the medical records of over 300 of Community Veterinary Outreach patients (to veterinarians, animals are the "patients", and the pet owners are "clients"), we found that 73 % of our patients were in ideal body condition score, compared to the household pets in the U.S. where it is estimated that 52.6 % of dogs and 57.6 % of cats are clinically overweight (2013 National Pet Obesity Awareness Day Survey 2014). In fact, studies have shown that most homeless pet guardians do not have trouble feeding their animal companions (Irvine et al 2012). In a survey of 332 homeless youth in Los Angeles, only 10.42 % of respondents indicated that it was hard to get pet food (Rhoades et al 2014).…”
Section: Companion Animals Of Street-involved Youthmentioning
confidence: 99%
“…Despite the many barriers to establishing and/or maintaining self-esteem for street-involved youth, Irvine et al (2012) have shown that pet ownership by homeless pet guardians helps to create a positive sense of self. Homeless pet owners described challenging public stigma of what good pet ownership looks like by demonstrating their ability to feed, care, and provide for their pets constant companionship and a freedom that housed pets are limited to.…”
Section: Human-animal Attachment-a Determinant Of Healthmentioning
confidence: 99%
See 3 more Smart Citations